Experimental Evaluation of the Hypersensitivity Reactions of a New Glycopeptide Antibiotic Flavancin in Animal Models - Michael I. Treshchalin; Vasilisa A. Polozkova; Elena I. Moiseenko; Andrey E. Shchekotikhin; Svetlana A. Dovzhenko; Mikhail B. Kobrin; Eleonora R. Pereverzeva (MDPI AG, 2023)
Glycopeptide antibiotics are still in demand in clinical practice for treating infections caused by resistant gram-positive pathogens; however, their use is limited due to severe adverse reactions. Their predominant types of side effects are immunoglobulin E-mediated or nonmediated hypersensitivity reactions. Therefore, the development of new glycopeptide antibiotics with improved toxicity profiles remains an important objective in advancing modern antimicrobial agents. We investigated a new eremomycin aminoalkylamide flavancin, its anaphylactogenic properties, influence on histamine levels in blood plasma, pseudoallergic inflammatory reaction on concanavalin A and the change in the amount of flavancin in the blood plasma after administration. It has been shown that flavancin does not demonstrate anaphylactogenic properties. The injection of flavancin resulted in a level of histamine in the blood three times lower than that caused by vancomycin. The therapeutic dose of vancomycin led to a statistically significant increase in the concanavalin A response index compared to flavancin (54% versus 3.7%). Thus, flavancin does not cause a pseudo-allergic reaction. The rapid decrease in flavancin concentration in the blood and the low levels of histamine in the plasma lead us to assume that any pseudoallergic reactions resulting from flavancin application, if they do occur in clinical practice, will be significantly less compared to the use of vancomycin.